KUALITAS EGGURT KERING DENGAN BAHAN DASAR SUSU DAN BERBAGAI MACAM BIJI-BIJIAN - Indratiningsih (Indratiningsih); Nurliyani (Nurliyani); Rihastuti (Rihastuti); Endang Wahyuni; Widodo (Widodo) (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
This study aimed to determine the chemical, sensory, and microbiological quality of eggurt that was mixed with various grains of sesame, green bean, and black soybean. The addition of grains starch was intended to improve thechemical and sensory quality, as well as to maintain the viability of lactic acid bacteria (LAB) during drying. Eggurt was prepared by fermented milk and albumen inoculated with 5% Lactobacillus bulgaricus and Streptococcusthermophillus (1:1) and incubated at 42°C to form a curd or the pH reached 4.5. Milk and albumen were pasteurized separately. Milk was pasteurized at temperature of 85°C for 30 minutes, while the albumen was pasteurized attemperature of 63°C for 5 minutes. Dried eggurt was produced by mixing of eggurt and blended grain with a ratio of 2:1, and then dried at 50oC for 16 hours. After dried, the eggurt products were then sampled for chemical, sensory andmicrobiological analysis. The results showed that eggurt mixed with sesame seeds had a highest score on texture (47.50), aceptability (43.06) and total lactic acid bacteria (5.67 log CFU/g) than eggurt mixed with black soybeans andgreen beans, while eggurt mixed with black soybean had a highest score (P<0.01) on acidity (43.85), fat (9.13%) and protein content (33.06%). There was no different effect between grain sources on degree of sweetness, lactoseconcentration, pH and acidity levels. It can be concluded that eggurt-sesame has the best sensory and microbiological quality, while the best chemical quality was obtained from eggurt-black soybeans.(Keywords: Quality, Dried eggurt, Milk, Sesame, Green beans, Black soybeans)